REVIEW TENTANG STUDI PEMODELAN MAKRO EKONOMI DI INDONESIA - Budhiasa, Gede Sudjana (Buletin Studi Ekonomi; Vol 17.No.2.Agustus 2012 (PP.99-225))
Abstract : Review of Indonesia’s Macroeconometris Model. The study reviews of some econometric modeling that developed by Bappenas, BKF Kemenkeu RI and Bank of Indonesia have been used some different instrument but with the same target goals such as low and stable inflation and together with economic growth as well. However, the different styles of macroeconomic model of those institutions can bee seen as the difference of institutions mission and targets. The model that were developed of different macroeconomic style models. Bappenas was developed a Mundell Fleming macroeconomic model that have characterized with small country argument related to international mobility of capital. The MODFI of BKF Kemenkeu tends to organized the government budgetary strategy based on taxes intervention to private consumption, investment and economic growth.  On the other hands, MODBI of Bank Indonesia macroeconomic model is strongly focused on monetary instrument of interest rate and foreign exchange rate as policy variable of handling the trade-off between inflation and economic growth. We can conclude that all those of the model studied categorized as large macroeconomic models that might be fail to capture some substantial strategic issues, therefore have look as the weakness of accuracy model in guidance decision making process. Finally, that the large scale macroeconomic model could be face some difficulties especially in finding the robust significant parameter estimates, and might be set-up  those of the models become less valuable in academic responsiblity. Abstrak : Review Tentang Studi Pemodelan Makro Ekonomi Di Indonesia. Kajian tentang pemetaan pemodelan ekonomi makro diperoleh dari Bappenas, BKF Kemenkeu, dan Bank Indonesia. Ketiga institusi tersebut memiliki kesamaan target  ekonomi makro, yaitu mengendalikan Philip curve untuk mencapai pertumbuhan ekonomi dan stabilitas inflasi sekaligus. Meskipun demikian, ketiga lembaga menggunakan pilihan penggunaan instrumen kebijakan yang berbeda. Bappenas menggunakan optimalisasi sumber daya melalui peranan politik APBN dan kebijakan moneter, untuk mencapai target ekonomi makro dengan mengembangkan konsep pemodelan Mundell Fleming macroeconomic model . Kemenkeu RI lebih terfokus kepada kebijakan fiskal dalam rangka menggerakkan pasar konsumsi domestik, investasi, dan dinamika perdagangan internasional. Model ekonomi makro Badan Kebijakan Fiskal Kemenkeu tampaknya lebih mendekati pemodelan yang dikembangkan di sejumlah negara Eropa, khususnya  pada kerja sama ekonomi Benelux ( Belgia, Nederland, Luxemburg). Pemodelan yang sangat fiscalist lebih memfokuskan kepada pemberdayaan ekonomi regional melalui politik anggaran APBN. Berbeda dengan pemodelan makro ekonomi dua lembaga diatas, maka Bank Indonesia mengembangkan MOBDI, dengan memilih instrumen suku bunga domestik dan nilai tukar. Keduanya sebagai instrumen dalam rangka mengelola kebijakan moneter mencapai tujuan akhir. Kata kunci : model makro, agregatif, model ekonometrika
Keywords: model makro, agregatif, model ekonometrika